Влияние на теплопередачу в пульсационной тепловой трубе ее ориентации в пространстве - Naumova, A. M.; Kravets, V. Yu. (PE "Politekhperiodika", Book and Journal Publishers, 2010)
The paper presents the results of experimental research of orientation effect on heat transfer characteristics of a pulsating heat pipe (PHP). It is shown that transport of either mass or heat depends on PHP orientation against its axis. As a consequence of comparing experimental data with other authors’ results, it was concluded that PHP thermal resistance depends not only on orientation but on some other determine factors such as device construction and thermophysical properties of heat carrier.